Pharyngeal tuberculosis. A care report. - Supomo Sukardono, Supomo Sukardono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Pharyngeal tuberculosis is a rarely diagnosed case or it is frequently ignored and confused with other diseases such as midline granuloma and fungal infections.Pharyngeal tuberculosis generally follows pulmonary tuberculosis while the incidence of pulmonary tuberculosis is still high.This report showed a male with distinct symptoms such as painful swallowing for 5 months and had small and shallow ulcers with rough edge and granulation tissue at the base, pale mucosa at the dorsal wall of pharynx, tonsils and soft palate. The differential diagnosis were midline granuloma, fungal infection and pharyngeal tuberculosis.The appropriate diagnosis of pharyngeal tuberculosis could be confirmed by the finding of a positive acid fast bacteria test or histopathological examination which showed pharyngeal tuberculosis. The patient was referred to the Pulmonary Disease Unit for treatment. After one month treatment the clinical features were better.Key words : tuberculosis - midline granuloma - fungal infection - pulmonary tuberculosis